Tinjauan Hukum Islam Tentang Transaksi Penangguhan Bahan Bangunan Dengan Uang Di Muka - Sunarsa , Sasa; Kholifah, Nurul (Jurnal Hukum Ekonomi Syariah, 2023)
Building materials are certainly needed by the local community, be it for people who will build houses or renovate houses. Usually, consumers choose building stores that provide complete building materials and affordable prices, also with good quality. But store owners not only provide quality goods and affordable prices, store owners must have other marketing techniques to attract customers to shop at their stores. The development of building stores in transactions is very diverse, one of which is by making payments first, but the goods are not taken at that time, but later when building materials are sufficient. The formulation of the problem in this study is how is the pricing mechanism for building material deferral transactions with money in advance? how Islamic law reviews the transaction of deferral of building materials with money in advance. So this study aims to find out what building material deferral transactions are, pricing mechanisms in building material deferral transactions with advance money and Islamic law review of building material deferral transactions with advance money. This research is included in the type of qualitative research with the collection techniques used, namely interviews, observation and documentation. From this data is analyzed through the stages of data reduction, data presentation, then conclusions. Based on the results of this study, it is known that buying and selling building materials with an advance money system at building shops in Tarogong Kaler District is related to the opinion of scholars who allow the sale and purchase, then buying and selling and selling transactions carried out in building shops are allowed. While the contract used in the transaction of deferral of building materials with money in advance is a greeting contract.  Keywords : Islamic Law, Transaction, Suspension, Building Materials, Money Up Front